Deskripsi Kreativitas Siswa dalam Menyelesaikan Soal Literasi Geometri - Mulbar, Usman; Alimuddin, Alimuddin; Chinsa, Nurhusneini (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This research aims to describe students' creativity in solving geometric literacy problems based on initial abilities. The population of this research were students of class IX MTs Negeri 3 Enrekang. The researcher used purposive random sampling and obtained 86 students who described quantitatively and 6 students who described qualitatively. The data collection technique is distributed an initial mathematical ability test and a creativity test for geometry. The instruments of this research are the early equivalents of mathematics, the creativity of geometry tests, and the guidance of interviews. This research is qualitatively and quantitatively. The results of this research are from 86 students solving problems related to the surface area and volume of prisms, 36 students fulfilled the fluency indicators, 30 students fulfilled the flexibility indicators, 11 students fulfilled the novelty indicators, and 39 students did not fulfil the three creativity indicatorss. Then from 86 students solving problems related to the surface area and volume of pyramids, 25 students fulfilled the fluency indicators, 22 students fulfilled the flexibility indicators, five students fulfilled the novelty indicators, and 34 students did not fulfil the three creativity indicatorss.